One Stop Service for Asthma Patients Care by a Multidisciplinary Team of Buriram Hospital - Modthong, Wisagorn; Mayurasakorn, Songsak; Rukpanich, Punnipa; Junla-or, Panomporn; Tarasaowarop, Pernjit (Journal of Health Science of Thailand, 2017)
Asthma is a chronic disease and number of asthmatic patients had increased to more than four million asthma patients in Thailand and 5 percent mortality was reported. The Ministry of Public Health has a policy that all hospitals services are provided by 3D system, so Buriram’s outpatient unit set up a multidisciplinary team providing integrates care- One Stop Service. This descriptive research studied 250 adult asthma patients who were regularly undergoing treatment at Asthma clinic during January 1, 2009 - December 31, 2010. Data were analyzed by using percentage, mean, and standard deviation. The results showed that patient admission decreased 60 percent, ER-visit also decreased 64.71 percent and the ≥ 80 percent of PEFR (Peak Flow Expiratory Rate) increased from 87.67 percent to 89.35 percent. After “One Stop Service” was implemented, the average time spent at Adult Asthmatic Clinic decreased by 1.16 hours. Expenses on medical treatment decreased by 62,053.30 bath and satisfaction rate increased to 95.40 percent. Therefore, this 3D system service allows patients to control asthmatic symptoms better, more easy access resulting in higher patients’ satisfaction and less medical care expense. This service model can be provided to other asthma patients in order to increase the service accessibility. Moreover, it can be applied to other patient groups such as hypertensive and stroke.